Narrativas sobre comunicación, límites, roles y jerarquía en un grupo de madres parejas de militares (2017)
The objective of this research is to describe the narratives about communication, limits, roles and hierarchy of a group of soldiers’ wives during their duty and stay at home. The theoretical underpinnings of this research are based on the systemic approach; where an interpretive analysis of the narratives of each of the interviews is done by means of a qualitative matrix which allowed to sort and classify the information. Thus, it was possible to demonstrate significant emerging categories within the research. The methodology used in this project is qualitative; the participants were 4 soldiers’ wives of the national army of Colombia which met the criteria required. As data collection technique the open interview was used. The results allowed the researchers to describe these military families as functional families; since due to the hard work militaries have to face and their constant in duty leaves from home, the responsibility regarding the authority, rules, standards and limits are carried out but their women; including taking care of themselves.